Evaluating a multimodal digital book's impact on ESP students' learning outcomes - Laksana, I Putu Yoga; Padmadewi, Ni Nyoman; Suarcaya, Putu; Utami, I.G.A Lokita Purnamika; Ramendra, Dewa Putu (UPT Bahasa Universitas Tanjungpura, 2024)
The use of digital books in EFL setting has become widespread, eliciting responses. However, the evaluation on the multimodal digital book using a Kirkpatrick model of evaluation is limited. This study focused on the evaluation of the use of multimodal digital book in English for Business Course toward the students